The Ecological Justice in the Discourse of Islamic Group: insight from Indonesian Religious Organization - Zahra, Fathimatuz; Arifin, Zainul; Hakim, M Nasrul; Adi, Brian Trinanda Kusuma (FIKRAH, 2026)
Environmental issues have become a global issue that is not only a concern for the government but also religious organizations. This article examines the discourse on environmental damage and ecological justice within Islamic organizations in Indonesia, focusing on both moderate organizations (Nahdlatul Ulama and Muhammadiyah) and transnational movements (Islamic Defenders Front, Hizbut Tahrir Indonesia, and Muslim Brotherhood affiliates). The study aims to complement existing literature that often treats Islamic environmentalism as monolithic or organization-specific by mapping diverse responses to environmental damage and analyzing how these responses implicitly and explicitly shape environmental management. Using a qualitative comparative analysis of organizational documents, congressial decisions, and programmatic actions, the article identifies distinct yet complementary discourses: NU’s fiqh al-bi’ah (environmental jurisprudence) declaring pollution haram; Muhammadiyah’s Fiqh of Water and food estate programs; and transnational movements’ disaster response institutions and tree-planting initiatives. The findings reveal that despite ideological differences, all these organizations contribute to ecological justice, a concept that collectively handles environmental protection while minimizing inter-organizational ego. Theologically, the study advances the recognition of ḥifẓ al-bi’ah (environmental protection) as a sixth essential objective (maqṣad sadis) within maqaṣid al-shari’ah, strengthening the religious basis for ecological activism. The article’s key contributions include a comparative framework across moderate and transnational spectrums, the introduction of ecological justice as an analytical lens, and practical pathways for inter-organizational collaboration to address Indonesia’s pressing environmental challenges.